(untitled) (Research, Society and Development, 2022)
The present investigation discusses the possible articulations between Digital Technologies of Information and Communication (DTICs) and Early Childhood Education. Thus, a continuing education course for education professionals was structured and implemented for 111 professionals who worked in this segment in a municipality in the interior of the state of Espírito Santo. In this research, we will focus our discussions on the possible dialogue between the DTICs, the teaching practices developed for children included in Early Childhood Education, aiming to understand how the teachers appropriated the activities from the narratives of two trainer teachers who followed all the actions developed in this training. From the perspective of qualitative narrative research, the trainers pointed out a series of learning experiences and possible intertwinings between technologies and early childhood education, demonstrating the need for Technological Literacy for Education professionals and for continuing education courses.